Association Of Workplace Culture, Stress and Depression Among Civil Servants in The Ministry of Health, Akure, Ondo State - Akpunne , Bede Chinonye; Dosumu , Andrew Tunade; Ogundipe , Enioluwa (Corpus Intellectual, 2025)
Organizational work culture is a construct that is seen to exist in every single organization, association, and group that seeks to carry out one form of work or the other. Civil servants also experience particular types of work culture which if not properly observed, managed and evaluated could lead to the existence of depression and stress among these workers. Literature suggests that Organizational work culture and job environment is major predictors of depression and stress that could exist in work staff and employees. This study adopted the use of Purposive sampling technique and a total of 242 civil servants from the Ministry of Health in Akure, Ondo state were selected for this study, Zung Self-rating Depression Scale, Perceived Stress Scale and Organizational Culture Assessment Scale were used for data collection for this study. Regression and independent-t-test were used to test for the hypothesis of this study. This study revealed that the prevalence of depression was 9% and stress 23% among the participants. Factors of organizational work culture types (Clan, Adhocracy, Market and hierarchy) jointly significantly predicted depression among the participants [F (4,237) =6.06, P<.01]. Factors of organizational work culture (Clan, Adhocracy, Market and hierarchy) types also jointly significantly predicted stress among civil servants in the Ministry of Health in Ondo state [F= ( 4, 237) =17.95,P<.01. Findings also revealed that gender difference and age had no significant influence on depression and stress among the participants .The conclusions drawn proved that there was a significant relationship between organizational work culture, depression and stress among civil servants in Ondo state metropolis and therefore the work culture practiced in the civil service must be revised and put in evaluation constantly. Furthermore, continuous effort must be made to identify factors that can trigger depression and stress among workers aside from the work culture in an organization alone.